Pengembangan Lembar Kerja Peserta Didik Dengan Pendekatan Matematika Realistik Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SMA Di SMA Negeri 2 Kabanjahe (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This research aims to produce an LKPD product with a realistic mathematical approach that is valid, practical and effective for improving students' mathematical communication skills. This research and development is based on the stages of the 4D development model by Thiagarajan which was adapted to 3D including the definition, design and development stages. The subjects in this research were the X-Mipa 1 class of SMAN 2 Kabanjahe, totaling 30 people. Based on the research conducted, the validity of the LKPD obtained an average assessment of 89.47% by material experts and 88.15% by media experts with very valid qualifications. Through a questionnaire on the practicality of LKPD by teachers and students, an average of 90.27% was obtained by teachers and 92.12% by students with very practical qualifications. The implementation of learning by applying LKPD with RME was carried out to see the effectiveness of LKPD in obtaining results, namely achieving classical learning completeness. 86.67%, achievement of learning objectives was achieved in questions 1,2,3,4 and 5 and achievement of efficient learning time, from the effectiveness assessment reference, the LKPD developed was classified as effective. The increase in mathematical communication skills that occurred was an increase in the moderate category with an average gain score of 0.632. Based on the data obtained, it was concluded that the LKPD with RME that was developed met the qualifications of being valid, practical and effective.